Ultrasonographic Assessment of Intrinsic Vascularity in Choroidal Nevus, Suspicious Choroidal Nevus, and Choroidal Melanoma - Buse Guneri Beser, MD; Tanya McClendon, CDOS; Bernadete Ayres, MD; Hakan Demirci, MD (Ophthalmology Science)
Purpose: To determine if intrinsic vascularity can be observed in B-scan ultrasound examinations of choroidal nevi (CN) and compare the intensity of the vascularity among CN, suspicious choroidal nevi (SN), and choroidal melanomas (CMs). Design: A prospective nonrandomized comparative trial. Participants: Patients with CN, SN, or treatment-naive CM. Methods: From September 2016 to January 2023, all patients underwent ultrasound examination using 10- or 15-MHz B-scan probes at a tertiary ocular oncology service. Main Outcome Measures: Observed intrinsic vascularity on B-scan examinations. Results: Forty-three eyes with CN, 49 with SN, and 45 with CM were included. We evaluated the areas of flickering motion inside the lesions on B-scan ultrasonography (USG) videos. Intrinsic vascularity was detected in 37 (86%) CN, 43 (88%) SN, and 45 (100%) CM. The intensity of intrinsic vascularity was moderate in 58% of CN but high in 45% of SN and 73% of melanomas. In the combined group (nevus and melanoma), the degree of intensity of intrinsic vascularity demonstrated a positive correlation with subretinal fluid and the lesions` height and basal diameter. In contrast, a negative correlation was observed between the degree of intensity of intrinsic vascularity and internal reflectivity and the presence of overlying drusen. Conclusions: Choroidal nevi can have moderate intrinsic vascularity, detectable during B-scan ultrasound examinations. This contradicts the current view that CN is a nonvascular tumor on ophthalmic ultrasound. Therefore, the identification of vascular motion in B-scan USG cannot be used to exclude the diagnosis of CN. Serial multimodal imaging along with a clinical follow-up is necessary for the differentiation of CN and melanomas. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.